Hybridization of photocatalytic fuel cell with oxygen nanobubbles: A synergistic approach for energy-efficient degradation of azo dye - Nurhafizah, Mohd Selihin; Tay, Meng Guan (Elsevier Ltd., 2026)
Advanced oxidation processes (AOPs) are currently being extensively studied, specifically photocatalytic fuel cells (PFCs) and nanobubble technology. However, the performance of PFC decreases at higher pollutant concentrations. Hence, this study investigated the hybridization of PFC and oxygen nanobubbles (PFC/O2NBs) for treating azo dye wastewater. Four key parameters: contact time, initial concentration, pH, and light intensity were optimized using methyl orange as synthetic azo dye. Meanwhile, oxygen nanobubbles (O2NBs) were analyzed using a Zetasizer Nano, and the bubble size was confirmed to be in the range of 49.3 to 387.9 nm, with moderate stability (ζ-potential = -11.4 to -15.0 mV). Results showed that the individual PFC achieved 69.1% removal efficiency under optimized conditions, whereas O2NBs showed complete degradation (100%) under optimum conditions of 3 h, due to enhanced DO levels (66%). The hybrid PFC/O2NBs system exhibited much greater performance, achieving complete degradation (100%) within 10 min with 34% increase in DO concentration. In addition, the hybrid PFC/O2NBs system demonstrated higher electricity generation (Pmax = 139.201 μW cm-2) and improved energy efficiency, with significantly lower energy consumption (EEO = 2.53 kWh.m-3.order-1) compared to the individual systems. The synergistic index further confirmed the superior performance, with contact time showing the highest (f = 24.11).